ANALISIS INOVASI PRODUK, PEMASARAN DAN KOLABORASI (IP2K) KUNCI KEBERHASILAN UMKM PASCA PANDEMI COVID-19 - Tri Widodo; Bertha Kusuma Wardani; Yogi Hermawan (Sekolah Tinggi Ilmu Ekonomi Semarang, 2022)
Micro, Small, and Medium Enterprises (MSMEs) are sectors that have been affected by the Covid-19 pandemic. The pandemic in Indonesia has been going on for approximately two years, so it must be addressed with some adaptations to survive it. The impact of the pandemic on MSMEs in Indonesia is relatively high, reaching 87.5% according to the Minister of State-Owned Enterprises (SOEs) statement, which means that only 12.5 feel the impact is relatively small. Digitalization is a solution for SMEs as a business strategy to survive in the new normal era since the pandemic has changed people's behavior and the business competition map. Collaboration with digitalization can be done with Collaborative Marketing. This study aims to find how MSMEs can apply solutions to rise after the Covid-19 pandemic and identify product innovation, marketing, and collaboration (IP2K) factors that play a role in growing MSMEs so that they have a competitive advantage. The results show that only MSMEs that carry out product innovation, implement appropriate marketing strategies, and collaborate can successfully survive and develop their businesses. So that as the key to the success of MSMEs after the pandemic, MSMEs must innovate products, implement appropriate marketing strategies, and collaborate in developing their businesses.